Effect of Intra-Canal Direct Current Electric Stimulation on Orthodontic Tooth Movement: An Experimental Study in Canines - Showkatbakhsh, Abdolrahman; Younessian, Farnaz; Dianat, Omid; Izadi, Seyed Sadra; Badiee, Mohammadreza; Showkatbakhsh, Mehrdad; Akbarzadeh Baghban, Alireza (Journal of Dental School, 2019)
Objectives: The purpose of this study was to evaluate whether intra-canal application of controlled direct electric current (DEC) could accelerate the amount of orthodontic tooth movement (OTM) in young adult mixed breed dogs. Methods: Fourth premolars of both jaws of five young adult mixed breed dogs were divided into two groups of control and experimental groups. Orthodontic force was applied to both groups using an active NiTi push coil spring. Direct electric stimulation (15µA DC) was conducted by intra-canal usage of electric potential (1.5v). The experimental teeth were compared with controls in terms of clinical OTM results measured with an electronic caliper every two weeks (four time intervals). The animals were sacrificed one month (T2) or two months (T4) after initiation; and tissue sections were decalcified for histological evaluation. The data were analyzed using SPSS 16, Shapiro-Wilk test and paired t-test. Results: Measurements revealed a statistically significant increase in OTM at electrically stimulated sites compared to the control sites in just one time interval (T3: after four weeks) (P< 0.05). Histological sections also showed increased osteoblastic and osteoclastic activity at tension and compression sides of the experimental group compared to the control group, respectively at both time intervals (T2 and T4). Conclusion: Direct intra-canal electric current applied by a miniature electric device is effective for increasing the rate and amount of OTM in canine experimental model.